2019
DOI: 10.21273/jashs04694-19
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Mapping of Eastern Filbert Blight Resistance Quantitative Trait Loci in European Hazelnut Using Double Digestion Restriction Site Associated DNA Sequencing

Abstract: European hazelnut (Corylus avellana L.) is an economically important edible nut producing species, which ranked sixth in world tree nut production in 2016. European hazelnut production in the United States is primarily limited to the Willamette Valley of Oregon, and currently nonexistent in the eastern United States because of the presence of a devastating endemic disease, eastern filbert blight (EFB) caused by Anisogramma anomala (Peck) E. Muller. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…The DNA sequences of a set of previously developed SSR markers on LG2 and LG7 (Table 2) were aligned with the 'Jefferson' genome (V2) assembled from PacBio sequences (Snelling et al, 2018). In addition, 28 double digest restriction site associated DNA sequencing (ddRAD-Seq) markers with positions from 2.57 to 24.76 cM on LG2 were aligned with the V2 'Jefferson' reference genome, of which RUCaS1_18603 and RUCaS1_14004 flanked the EFB resistance quantitative trait locus (QTL) in Rutgers University selection H3R07P25 from Holmskij, Russia (Honig et al, 2019). The alignment of the marker sequences with the V2 genome sequence identified contigs associated with the EFB resistance regions on these two LGs, and the contigs were mined for SSR motifs > 16 bp using the GMATo program (Wang et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA sequences of a set of previously developed SSR markers on LG2 and LG7 (Table 2) were aligned with the 'Jefferson' genome (V2) assembled from PacBio sequences (Snelling et al, 2018). In addition, 28 double digest restriction site associated DNA sequencing (ddRAD-Seq) markers with positions from 2.57 to 24.76 cM on LG2 were aligned with the V2 'Jefferson' reference genome, of which RUCaS1_18603 and RUCaS1_14004 flanked the EFB resistance quantitative trait locus (QTL) in Rutgers University selection H3R07P25 from Holmskij, Russia (Honig et al, 2019). The alignment of the marker sequences with the V2 genome sequence identified contigs associated with the EFB resistance regions on these two LGs, and the contigs were mined for SSR motifs > 16 bp using the GMATo program (Wang et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Resistance in 'Ratoli' from Spain (Sathuvalli et al, 2011a), C. americana 'Rush', and interspecific hybrid 'Yoder #5' (Bhattarai et al, 2017b) was assigned to LG7. Resistance from OSU 759.010 from the Republic of Georgia and Rutgers University selection H3R07P25 from Holmskij, Russia was assigned to LG2 (Honig et al, 2019;Sathuvalli et al, 2011b). Sathuvalli et al (2010) reported that Moscow selections #2 and #27 were EFB resistant following greenhouse inoculation.…”
mentioning
confidence: 99%
“…SSRs have been proven to be highly effective tools in assessing genetic diversity also in Corylus avellana L. [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. By these molecular markers, hazelnut germplasm collections have been fingerprinted, defining synonymies and homonymies [ 34 , 35 , 36 ], assessing genetic relationships and parentage [ 37 , 38 , 39 , 40 , 41 ], investigating the genetic structure of different populations comparing local cultivars and wild genotypes [ 29 , 32 , 38 , 42 , 43 ], and developing genetic maps for association analysis [ 44 , 45 ]. More recently, single-nucleotide polymorphisms (SNPs) based on next-generation sequencing (NGS) have been utilized in hazelnut linkage maps [ 46 , 47 ] to assess the genetic diversity and to investigate the domestication history of European hazelnut [ 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, resistance in ‘Ratoli’ from Spain, C. americana ‘Rush’ from Pennsylvania and interspecific hybrid ‘Yoder #5’ from Ohio was assigned to a region on LG7 ( Sathuvalli et al, 2011a ; Bhattarai et al, 2017a ). Resistance in selection OSU 759.010 from the Republic of Georgia and Rutgers University selection H3R07P25 from southern Russia was assigned to a region on LG2 ( Sathuvalli et al, 2011b ; Honig et al, 2019 ). Additional sources of EFB resistance have been identified, including Moscow #26 ( Sathuvalli et al, 2010 ), C. heterophylla ‘Ogyoo’ ( Coyne et al, 1998 ), and interspecific hybrid ‘Estrella #1’ ( Chen et al, 2007 ), as well as germplasm collected in Russia, Crimea and Poland ( Molnar et al, 2007 ; Capik et al, 2013 ; Leadbetter et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%